2011
DOI: 10.1038/nature10224
|View full text |Cite
|
Sign up to set email alerts
|

Thermal spin current from a ferromagnet to silicon by Seebeck spin tunnelling

Abstract: Heat generation by electric current, which is ubiquitous in electronic devices and circuits, raises energy consumption and will become increasingly problematic in future generations of high-density electronics. The control and re-use of heat are therefore important topics for existing and emerging technologies, including spintronics. Recently it was reported that heat flow within a ferromagnet can produce a flow of spin angular momentum-a spin current-and an associated voltage. This spin Seebeck effect has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
246
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 224 publications
(259 citation statements)
references
References 24 publications
13
246
0
Order By: Relevance
“…spin accumulation) in nonmagnetic SC is a central issue of SC-based spintronics 1,3-5 . Significant progress has been made on the spin accumulation in various SC systems by means of circularly polarized light 4,6 , spin-polarized tunneling 7-13 , hotelectron spin filtering 14,15 , spin-orbit interaction 16,17 , or magnetization dynamics 18,19 .Intriguingly, Le Breton et al 20 have reported a rather different mechanism for the spin accumulation, in which temperature difference across a ferromagnet (FM)/oxide/SC tunnel contact can induce the spin accumulation (Dm) in SC via Seebeck spin tunneling (SST). It was found that the SST effect, involving thermal transfer of spin angular momentum from FM to SC without a tunneling charge current, is a purely interface-related phenomenon of the tunnel contact and governed by the energy dependence of its tunnel spin polarization (TSP) 20 .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…spin accumulation) in nonmagnetic SC is a central issue of SC-based spintronics 1,3-5 . Significant progress has been made on the spin accumulation in various SC systems by means of circularly polarized light 4,6 , spin-polarized tunneling 7-13 , hotelectron spin filtering 14,15 , spin-orbit interaction 16,17 , or magnetization dynamics 18,19 .Intriguingly, Le Breton et al 20 have reported a rather different mechanism for the spin accumulation, in which temperature difference across a ferromagnet (FM)/oxide/SC tunnel contact can induce the spin accumulation (Dm) in SC via Seebeck spin tunneling (SST). It was found that the SST effect, involving thermal transfer of spin angular momentum from FM to SC without a tunneling charge current, is a purely interface-related phenomenon of the tunnel contact and governed by the energy dependence of its tunnel spin polarization (TSP) 20 .…”
mentioning
confidence: 99%
“…Intriguingly, Le Breton et al 20 have reported a rather different mechanism for the spin accumulation, in which temperature difference across a ferromagnet (FM)/oxide/SC tunnel contact can induce the spin accumulation (Dm) in SC via Seebeck spin tunneling (SST). It was found that the SST effect, involving thermal transfer of spin angular momentum from FM to SC without a tunneling charge current, is a purely interface-related phenomenon of the tunnel contact and governed by the energy dependence of its tunnel spin polarization (TSP) 20 .…”
mentioning
confidence: 99%
See 3 more Smart Citations